Multi-Input CNN for Vision-Based In Situ Analysis of Extraterrestrial Surface Composition - MARCINIAK, Kacper; GRZESIAK, Michał; ZAWORSKI, Igor; PAWLISZEWSKI, Dominik; ZYGARLICKA, Dominika; WNUK, Michał; ZAKRZEWSKI, Adrian (Computer Assisted Methods in Engineering and Science, 2025)
Earth’s natural resources are finite, which is why engineers and scientists are increasingly directing their attention to the extraction of materials from celestial bodies. Beyond the extraction itself, however, a major challenge remains the localization of valuable substances and the assessment of their quality in situ. In this article, we present a flexible and robust method for estimating the content of selected components in heterogeneous mixtures using RGB image processing. The proposed deep learning architecture achieves high prediction accuracy with root mean squared error (RMSE) of (0.190 ±0.024) %. The framework supports a variety of backbone architectures, including lightweight models, making it suitable for deployment on edge devices such as planetary rovers. Furthermore, the method is flexible, allowing for easy adaptation to other tasks, for example, the analysis of more complex mixtures or inference based on multi- or hyperspectral imagery.